Optimalisasi Program Pengawasan Sekolah dan Kompetensi Pengawas Untuk Meningkatkan Mutu Pendidik - Fajar Ainol Yakin; Qoidul Khair (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This study aims to analyze the school supervision program and the competence of supervisors in an effort to improve the quality of educators. The school supervision program is designed as a guideline for the implementation of the main tasks and functions of supervisors, which include academic supervision, managerial supervision, educational evaluation, as well as coaching principals and teachers in the assisted schools. Competencies required by supervisors include personality, managerial skills, academic supervision skills, educational evaluation, and research and development skills. This study emphasizes the importance of sustainable and planned supervision by referring to the results of previous supervision and prevailing education policies. The findings show that the implementation of an effective supervision program supported by the competence of qualified supervisors can improve the quality of the learning process and the performance of educators in the assisted schools. Thus, strategic supervision is a key factor in creating a quality education system.